Trends in the Surgical Treatment of Articular Cartilage Lesions in the United States from 2007 to 2016 - DeFroda, Steven F.; Bokshan, Steven L.; Yang, Daniel S.; Daniels, Alan H.; Owens, Brett D. (The Journal of Knee Surgery, 2020)
Management of cartilage lesions of the knee can be complex, time consuming, and controversial, especially without a widely agreed upon “gold-standard” management. The PearlDiver database (www.pearldiverinc.com, Fort Wayne, IN) was queried for surgical management of cartilage lesions specified by Current Procedure Terminology (CPT) codes: 29877, chondroplasty; 29879, microfracture/drilling; 29866, arthroscopic osteochondral autograft; 29867, arthroscopic osteochondral allograft; 27412, autologous chondrocyte implantation (ACI); 27415, open osteochondral allograft; or 27416, open osteochondral autograft. Procedures were categorized as palliative (chondroplasty), microfracture/drilling, or restorative (arthroscopic osteochondral autograft; arthroscopic osteochondral allograft; ACI; open osteochondral allograft; or open osteochondral autograft). Linear regression was performed to determine the significance of yearly trend across each procedure.From 2007 to 2016, a total of 35,506 surgical procedures were performed. The average yearly incidence was 7.8 per 10,000 patients. Overall, palliative techniques (chondroplasty) were more common (1.8:1 ratio for chondroplasty to microfracture and 34:1 ratio chondroplasty to restoration procedure). There was a trend of decreasing incidence of palliative procedures seen by a significant decrease in the ratio of palliative to microfracture/restorative procedures of 0.2512 each year from 2007 to 2016 (p < 0.001). This decrease followed a linear trend (R2 = 0.9123). In 2013, the number and incidence of the palliative procedures declined below that of microfracture procedures, with microfracture being most common from 2013 to 2016. Palliative chondroplasty was no longer the most commonly performed procedure for cartilage lesions in the United States from 2007 to 2016, as more surgeons opted for microfracture procedures instead. Restorative procedures (ACI, osteochondral autograft transfer system) remained unchanged over the study period, in accordance with the sports medicine literature; however, early functional outcomes studies do show the equivalency and in some cases superiority compared with microfracture. This is Level III study.
Keywords: cartilage; chondroplasty; microfracture; ACI; OATS